Patient satisfaction with chemotherapy nursing care: A review of the literature - Susi Purwitasari; Chriswardani Suryawati; Cahya Tri Purnami (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Health efforts are a series of activities carried out in an integrated, integrated, and sustainable manner to maintain and improve the health status of the community. The quality or quality of health services can be seen from several perspectives, namely the perspective of the health service provider, the perspective of the funder, the perspective of the owner of health care facilities, and the perspective of the patient. Dissatisfaction with chemotherapy services included chemotherapy rooms that had toilets that were not clean and comfortable, nurses putting infusions with several punctures, unfriendly staff, menu display, and food variations that were less attractive.Purpose:  A review of the literature to analyze patient satisfaction with chemotherapy nursing careMethod: This study uses a literature study with the keywords patient satisfaction in the chemotherapy section of the hospital in a database from scientific publications Science Direct, Scopus, ProQuest, Springer Link, Google Scholar, JSTOR, and Emerald Insight with a population of 1180 articles over the last 5 years, then selected into 10 articles according to the inclusion criteria.Results: From 10 articles that matched the inclusion and exclusion criteria, it was found that several factors had a relationship with patient satisfaction in the chemotherapy department, namely the quality of the reliability dimension, the quality of the responsiveness dimension, the quality of the assurance dimension, the quality of the empathy dimension, and the quality of the tangible dimension.Conclusion: From a review of the results of most articles, it shows that there is a relationship between the Quality Dimension of Reliability, Quality of Responsiveness Dimension, Quality of Assurance Dimension, Quality of Empathy Dimension, Quality of Tangible Dimension with patient satisfaction in the chemotherapy section of the hospital